The Effect of Smartphone Use with Speech Delay Incidence in Toddlers in The Kapoiala Health Center Area, Konawe Regency - Sarce Rimpan; Mien Mien; Desiderius Bela Dhesa; I Wayan Romantika (LPPM STIKes Karya Kesehatan, 2022)
Abstract. Smartphone is a set of electronic devices that have various functions. Smartphones provide facilities that vary in terms of design and application so that it becomes an attraction for users to take the time to play smartphones. Today, many toddlers often use smartphones to play games rather than being used as a means of learning or playing outside. The purpose of this study was to determine the effect of smartphone use on the incidence of speech delay in children under five in the working area of ​​the Kapoiala Health Center, Konawe Regency. The sample in this study was toddlers as many as 57 people from a population of 205 people using the Accidental Sampling technique. The type of research used was a quantitative method with a cross sectional study design. The data collection technique used a research instrument in the form of a questionnaire. Data were analyzed using Fisher's exact test. The results showed that the low use of smartphones was 24 people (42.1%) and 33 people (57.9%), who were late with speech delay were 23 people (40.4%) and 34 people were normal ( 59.6%) and there is an effect of smartphone use with the incidence of speech delay in children under five in the working area of ​​the Kapoiala Health Center, Konawe Regency where the value of = 0.000 (<0.05)).